Simvastatin in traumatic brain injury: effect on brain edema mechanisms - Béziaud, Tiphaine; Ru Chen, Xiao; El Shafey, Nelly; Fréchou, Magalie; Teng, Fei; Palmier, Bruno; Beray-Berthat, Virginie; Soustrat, Mathieu; Margaill, Isabelle; Plotkine, Michel; Marchand-Leroux, Catherine; Besson, Valérie C (Critical care medicine, 2011)
Traumatic brain injury causes deleterious brain edema, leading to high mortality and morbidity. Brain edema exacerbates neurologic deficits and may be attributable to the breakdown of endothelial cell junction protein, leukocyte infiltration, and matrix metalloproteinase activation. These all contribute to loss of blood-brain barrier integrity. The pleiotropic effects of statins, hydroxymethylglutaryl-coenzyme A reductase inhibitors, may inhibit posttraumatic brain edema. We therefore investigated the effect of acute simvastatin on neurologic deficits, cerebral edema, and its origins. Randomized laboratory animal study. University-affiliated research laboratory. Male Sprague-Dawley rats. Rats were subjected to lateral fluid percussion traumatic brain injury. Our preliminary dose-effect study indicated that 37.5 mg/kg simvastatin, administered orally 1 hr and 6 hrs after traumatic brain injury, has the greatest anti-edematous effect. This dose was used to study its effects on brain edema and on its mechanisms. We first assessed the effects of simvastatin 24 hrs after traumatic brain injury on brain edema, brain claudin-5 expression, and the vascular endothelial-cadherin (pTyr731)/total vascular endothelial-cadherin ratio, matrix metalloproteinase-9 activity, intercellular adhesion molecule-1 expression, and polymorphonuclear neutrophil infiltration. We also evaluated blood-brain barrier permeability by measuring Evans blue and fluorescein sodium salt extravasation into the cerebral parenchyma. We then investigated whether simvastatin reduces neurologic deficits, edema, and blood-brain barrier permeability earlier than 24 hrs; these effects were evaluated 6 hrs after traumatic brain injury. The anti-edematous effect of simvastatin 24 hrs after traumatic brain injury was associated with increased claudin-5 and decreased intercellular adhesion molecule-1, polymorphonuclear neutrophil infiltration, and blood-brain barrier permeability, with no effect on matrix metalloproteinase-9 activity or vascular endothelial-cadherin phosphorylation. Earlier, 6-hrs after traumatic brain injury, simvastatin reduced neurologic deficits, cerebral edema, and blood-brain barrier permeability. Simvastatin could be a new therapy for reducing posttraumatic edema by preventing damage to tight junctions and neutrophil infiltration into the parenchyma, thus preserving blood-brain barrier integrity.